Superior visual rhythm discrimination in expert musicians is most likely not related to cross-modal recruitment of the auditory cortex - Korczyk, Maksymilian; Zimmermann, Maria; Bola, Łukasz; Szwed, Marcin (Frontiers in Psychology, 2022)
Training can influence behavioral performance and lead to brain reorganization. In particular, training in one modality, for example, auditory, can improve performance in another modality, for example, visual. Previous research suggests that one of the mechanisms behind this phenomenon could be the cross-modal recruitment of the sensory areas, for example, the auditory cortex. Studying expert musicians offers a chance to explore this process. Rhythm is an aspect of music that can be presented in various modalities. We designed an fMRI experiment in which professional pianists and non-musicians discriminated between two sequences of rhythms presented auditorily (series of sounds) or visually (series of flashes). Behavioral results showed that musicians performed in both visual and auditory rhythmic tasks better than non-musicians. We found no significant between-group differences in fMRI activations within the auditory cortex. However, we observed that musicians had increased activation in the right Inferior Parietal Lobe when compared to non-musicians. We conclude that the musicians' superior visual rhythm discrimination is not related to cross-modal recruitment of the auditory cortex; instead, it could be related to activation in higher-level, multimodal areas in the cortex.